PENGARUH HEURISTIK PADA KEPUTUSAN INVESTASI GENERASI MUDA DI KOTA DENPASAR - I Made Adhi Wirayana (Universitas Pahlawan Tuanku Tambusai, 2023)
Psychological factors can cause investors' irrational behavior in making decisions. This study aims to obtain empirical evidence of the effect of heuristic behavior on investment decisions. The data used in this study is primary data obtained through a survey conducted by distributing questionnaires to young people in Denpasar City, Bali Province, Indonesia who invest in the Indonesia Stock Exchange. The sample is determined by convenience sampling technique. Data analysis techniques use the structural equation model (SEM) with the Partial Least Square (PLS) software approach. The results of the study show that the heuristic influences the investment decision making of the younger generation in Denpasar City. Keywords: Heuristics, Investment Decisionsv